2006
DOI: 10.1038/sj.leu.2404458
|View full text |Cite
|
Sign up to set email alerts
|

ZAP-70 expression, as detected by immunohistochemistry on bone marrow biopsies from early-phase CLL patients, is a strong adverse prognostic factor

Abstract: Zeta-associated protein-70 (ZAP-70), mostly assessed by flowcytometry (FC), recently emerged as reliable prognostic factor in chronic lymphocytic leukaemia (CLL) at presentation. We evaluated ZAP-70 expression in 156 CLL patients by immunohistochemistry (IHC) on formalin-fixed bone marrow (BM) biopsies at diagnosis. At presentation, 117 patients (75%) were with Binet stage A, 27 (17%) stage B and 12 (8%) stage C. Median follow-up was 61 months (range 6-242). ZAP-70 was expressed in neoplastic lymphocytes of 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
(54 reference statements)
4
28
0
Order By: Relevance
“…In contrast, we found the difference in OS survival times for ZAP70 expression to be highly significant (P ϭ 0.0021). The median OS time for ZAP70 ϩ patients was 12.7 years, which is similar to previously reported findings (14,16,18 ). Only 3 studies have demonstrated a correlation between ZAP70 expression and OS; the other studies evaluated ZAP70's prognostic value only in terms of TFS.…”
Section: Zap70supporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, we found the difference in OS survival times for ZAP70 expression to be highly significant (P ϭ 0.0021). The median OS time for ZAP70 ϩ patients was 12.7 years, which is similar to previously reported findings (14,16,18 ). Only 3 studies have demonstrated a correlation between ZAP70 expression and OS; the other studies evaluated ZAP70's prognostic value only in terms of TFS.…”
Section: Zap70supporting
confidence: 87%
“…Patients with Ͻ20% ZAP70 ϩ B cells as measured by flow cytometry (FC) generally had a mutated IGHV status, and patients with Ն20% ZAP70 ϩ cells had an unmutated IGHV status. Further clinical studies confirmed the prognostic value of the ZAP70 protein (14)(15)(16)(17)(18)(19)(20); however, FC measurement of ZAP70 status is often inaccurate at the positivity limit (21 ) because of low resolution of the positive and negative populations, and can also be influenced by the gating procedure and antibody choice (22 ). To offset these drawbacks, investigators have proposed absolute quantification of ZAP70 mRNA (23,24 ).…”
mentioning
confidence: 99%
“…Therefore, we compared Hh member expression within prognostically relevant risk groups on the basis of Rai staging (Rai et al, 1975), immunoglobulin heavy chain variable gene mutational status, CD38 expression (Damle et al, 1999) and cytogenetic abnormalities (Dohner et al, 2000;Wiestner et al, 2003;Zanotti et al, 2007). We detected significantly higher SMOH expression in groups with unfavorable cytogenetic abnormalities compared with normal karyotypes (P ¼ 0.035), as increased SMOH expression was observed in patients with trisomy 12 (Tri12; Figure 2a).…”
Section: High-risk Cll Patients Express Increased Transcript Levels Omentioning
confidence: 85%
“…18 In this study, the expression of thioredoxin was not related to the mutated or unmutated status of IGHV genes. However, because few mutated cases were included, this may only imply that the potential leukemia growthpromoting effect mediated by thioredoxin is independent of the IGHV mutational status of the CLL patient.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 49%